Do customer knowledge and customer trust in IDIC affect bank customer retention? Evidence from Indonesia - Muhammad Simba Sembiring; Sisi Maghfirah Rahmah Sembiring (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The primary focus of this research was to examine the impact of customer knowledge and customer trust in Indonesia Deposit Insurance Corporation (IDIC) on the retention of bank customers in Indonesia.Method — The study employed a cross-sectional design and quantitative survey study. Questionnaires were distributed randomly to respondents via social media. 141 respondents from bank customers in Indonesia have been analyzed. Hypothesis testing is done by multiple linear regression analysis with structural equation modeling and SmartPLS as a statistical tool.Result — The results show that the average bank customer in Indonesia has sufficient knowledge about the role, function, task, and performance of IDIC. However, knowledge needs to be improved because some customers do not understand it well. The results provide empirical evidence that customer knowledge and customer trust in IDIC have positive influence on bank customer retention.Contribution — There is a new concept with the integration of two theories that will benefit future research. The findings contribute to addressing research gaps that have inconsistent results. The findings also contribute to improving customer knowledge and customer trust as a solution to the impact of the COVID-19 pandemic and the global financial crisis. This study supports the G20 in strengthening financial safety nets, where multilateral development banks are encouraged to strengthen their financing systems to face global economic challenges.